Persepsi Penonton Group Inclusive Tour Terhadap Pertunjukan Kecak Api Ramayana di Uluwatu - Widyasari, Nyoman Ari Trisna Dewi Manikan; Citrawati, Luh Putu; Swandewi, Ni Kadek (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
This study aims to find out the audience perception of the Kecak Api Ramayana performance in Uluwatu. The study is qualitative descriptive research using data that was collected through questionnaires and in-depth interviews. This study uses 100 samples which were determined using the Slovin formula with a 90% confidence level and a 10% error rate. The results show that audience group inclusive tour perception of the Kecak Api Ramayana performance in Uluwatu referred to a five-dimensional event with the average of marketing (4.32); transportation, access and guest reception (4,10); atmosphere, decoration and nuance (4.35); entertainment and activities (4.29); and facilities (3.78). Based on these five dimensions, the average of facilities dimension has the lowest score. Overall, the average dimension is at 4.17 with category “Good”.